Left ventricular output indices and sacubitril/valsartan titration: role of stroke volume index - Paolo Tolomeo; Ottavio Zucchetti; Emanuele D'Aniello; Noemi Punzo; Federico Marchini; Luca Di Ienno; Elisabetta Tonet; Rita Pavasini; Claudio Rapezzi; Gianluca Campo; Matteo Serenelli (ESC Heart Failure)
Abstract Aims This study aims to investigate the role of echocardiographically determined left ventricular output indices on sacubitril/valsartan titration in a cohort of outpatients with heart failure and reduced ejection fraction (HFrEF). Methods and results We analysed 106 HFrEF patients who underwent echocardiography examination up to 1 week before starting treatment with sacubitril/valsartan. For each patient, a comprehensive list of clinical and laboratory parameters was collected, and stroke volume index (SVi), cardiac index, and flow rate were calculated. The primary endpoint was the occurrence of complete titration of sacubitril/valsartan. The secondary endpoint was the incidence of adverse events (hypotension and renal adverse events). Univariate and multivariate logistic regression were used to identify variables associated with the primary and secondary endpoints. Mean age of patients was 73.7 ± 10.4 years, 72 patients (71.7%) had ischaemic aetiology of HF, and mean ejection fraction was 29.4 ± 5.9%. At multivariate analysis, SVi [odds ratio (OR) 1.43 per 5 mL/m2 increase, 95% confidence interval (CI) 1.03–1.97; P = 0.028], serum sodium (OR 1.18, 95% CI 1.02–1.37; P = 0.022), and haemoglobin (OR 1.73, 95% CI 1.25–2.40; P = 0.001) were found to be independent predictors of titration during follow‐up. Multivariate analysis for the secondary endpoint showed SVi (OR 0.63 per 5 mL/m2 increase, 95% CI 0.44–0.90; P = 0.012) and New York Heart Association Class III (OR 2.65, 95% CI 1.07–6.5; P = 0.034) to be associated with hypotension. Conclusions Stroke volume index is positively associated with complete titration of sacubitril/valsartan. Patients with low SVi are more prone to experience hypotension during titration